Comparative study of user friendliness of paperless partogram compared to WHO partogram in preventing prolonged labour - M., Faswila; Rao, Smitha B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Partogram is being used since 1954 when Friedman described it for monitoring progress of labour. The Paperless Partogram proposed by Dr. Debdas is a low-skill method for detection of abnormal labour. The objective of the present study was to know efficacy and user friendliness of paperless partogram in comparison with WHO partogram in monitoring and management of labour Methods: It’s a comparative study. Total of 100 patients were included in the study where half of the patients were monitored by paperless partogram and the other half by WHO modified partogram. The plotting of the WHO partographs started as soon the cervical dilatation was 4 cm along with regular painful uterine contractions. In the paperless partogram calculation will be two times, an ALERT ETD (estimated time of delivery) and an ACTION ETD. The outcome of labour will be recorded at the end of each partographs. Results: Paperless partogram was better than WHO partogram in terms of documentation, ease of use, learning, time factor, cost effectiveness and monitoring of labour, identification of abnormal labour. Conclusions: In present study paperless partogram was found to be preferred for monitoring of labour.